A DECONSTRUCTIVE READING TO FIND HOW PATERNALISM WORKS IN TEXTS FOR CHILDREN - Surya Sagiro Batubara; Burhan Nurgiyantoro; Widyastuti Purbani (Universitas Negeri Yogyakarta, 2023)
This is a qualitative descriptive study with the aim to find out how paternalism works in 12 Indonesian folktales by applying Derrida’s deconstruction theory. Twelve folktales from children books that represents theme about moral ideology were chosen as the objects of this study. Data collection did by document analysis. Data analysis then conducted by doing Derrida’s deconstruction analysis as proposed by Barry that involves verbal, textual, and linguistic analysis with the aim to investigate how paternalism works and give significant meaning in the folktales. The results that the paternalism seems to explain about pure paternalisms since the ideology closely related to give explanations about father (men) who completely takes control over children and women (wife). Even though the controls seems to be considered as for good reasons, this study proves the the paternalism show limitation of freedom and also reflects autonomous violation over women and children. The paternalism explains about men domination in public and domestic institution that legalize men to have power over women and children in domestic affairs. The paternalism supports men domination in culture and social institution, that makes men have power in marital institution and make marital life as women’ purpose in life in the name of norm and value in society. The paternalism also explains boy preference in marital affairs that explained discrimination over children.